Virtual reality interventions in the assessment and treatment of alcohol use disorder - a systematic scoping review on methodology - Olivia Gaddum; Stefan Gutwinski; Alva Lütt; Daa Un Moon; Anne Beck; Nadja Ruckser; Alessandro Turno; Robert Schöneck; Felix Bermpohl; Nikolaos Tsamitros (Addiction Science & Clinical Practice)
Abstract Background Virtual reality (VR) technology has been increasingly employed to develop innovative treatments for Alcohol use disorder (AUD) and overcome limitations of currents therapies. However, previous research in this field has yielded inconclusive results. To improve the quality and comparability of studies, a critical analysis of the research methodology employed in this field is necessary. Objectives This scoping review aims to provide an overview of existing studies with a focus on their objectives, methodology, treatment paradigms, and VR design characteristics. Methods A systematic literature research was conducted in the electronic databases MEDLINE (PubMed), APA PsychInfo, APA PsychArticles, PSYINDEX (EBSCOhost), Scopus, Web of Science and by search in the reference list of included publication to identify relevant publications. Clinical studies and study protocols using VR for the assessment or treatment of patients with AUD were included. Results The literature search yielded 1.197 studies, of which 22 met the inclusion criteria. Completed trials (n = 16) and study protocols (n = 6) were included. The majority of the studies (n = 19) used a VR cue exposure paradigm to induce craving. The studies can be classified either as assessment (n = 9) or treatment studies (n = 13). The duration (7–60 min) and number of applied sessions (1–13) varied significantly depending on the type of study. Craving outcomes were based on subjective and physiological measurements. All studies used alcoholic beverages and VR scenarios such as bars, pubs, parties and restaurants, with additional scenarios varying, except for one study using a hospital and subway scenario as aversive scenarios. Moreover, synchronized olfactory stimuli were frequently used. Conclusions Despite the heterogeneity of VR software features and VR interventions, it was possible to identify a similarity within the main VR scenarios employed, as well as consistent positive results concerning the induction of subjective craving by alcohol-associated VR cues. While VR interventions for AUD show methodological progress, future research should adopt standardized protocols, include objective psychophysiological outcomes, and evaluate long-term efficacy and feasibility in clinical settings. Integration of emerging VR paradigms and technologies may further enhance the therapeutic potential.